Stakeholders Collaboration Model in Integrated Waste Management in Gresik District, East Java (Nusantara Science and Technology Proceedings, 2021)
The right choice to solve problems that require quick action and requires the participation of many parties requires stakeholder collaboration. Collaboration is a bridge that can turn potential conflicts of interest between stakeholders into a very profitable development potential. Garbage is a big and complicated problem because it involves the lives of many people, including its management and processing. For this reason, the Gresik Regency Environmental Service (DLH) tried a way to realize its vision with collaboration between stakeholders. The purpose of this study was to map the driving and inhibiting factors in integrated waste management. The research method used is a qualitative descriptive approach where the data sources are obtained from secondary, literature studies, interviews, and field visits. Informants of the Head of the Department of Cleanliness and the Environment and their staff, the public and the private sector. The research focus is on mapping the driving and inhibiting factors in integrated waste management. The results showed that the driving and inhibiting factors originating from the systemic conditions of the Gresik Regency Government were not running proportionally in overcoming the problem of waste management.